Confirmed Delta Variant COVID-19 Infection at A Single Centre Tertiary Hospital: A Case Series - Sally Aman Nasution; Muhadi Muhadi; Eric Daniel Tenda (Acta Medica Indonesiana, 2022)
SARS-CoV-2 continues to mutate with the emergence of new variants. Variant B.1.617.2 (Delta) is a variant of concern with evidence of increased transmission, more severe disease, decreased effectiveness of treatment or vaccines, or failure of diagnostic detection. In this article, we report on the clinical and biological picture of the first confirmed delta variant COVID-19 infection in Indonesia. From May 31 to June 17, we identified ten cases with confirmed delta variant COVID-19 infection admitted to a tertiary academic hospital in Jakarta. All subjects that have been vaccinated presented with mild-moderate disease. Most patients present with initial respiratory complaints, without radiological abnormalities on chest x-ray examination, and an increase in C-reactive protein. Seven out of ten patients have been vaccinated; the three patients who had not been vaccinated experienced severe COVID-19 symptoms, two of whom died. Due to the increased transmission of this variant, we recommend vaccination, wearing a mask, and social distancing to reduce the impact of infection with delta variant B.1,617.2.